UNVEILING PINE RESIN CHEMISTRY - Barbosa, Regis Silveira; Gomes, Jadson da Silva; Amaral , Douglas Henrique Ferreira; de Oliveira, Nicole Aparecida Amorim; Pires, Otávio Augusto Pinheiro; da Silva, Maria Eduarda; Vaz, Carolina Ferreira; Couto, Laércio; Júnior Dias, Herbert; Heleno, Vladimir Constantino Gomes (Seven Editora, 2025)
Pine resins, mostly the ones provided by Pinus elliottii, are known to present interesting activities in biological systems and are commonly treated as promising source of active compounds. Due to our interest in Natural Product chemistry and in diterpenes, also known to be pine resins components, we developed this work about the chemical composition of those resins. The essential oil composition showed the presence mostly of - and - pinene, -phelandrene and -cimene. The non-volatile fractions showed dehydroabietic acid as the primary component and revealed other abietane diterpenes were less abundant. This study revealed that these resins are surely good sources of dehydroabietic acid for further chemical studies with this natural product.DOI: https://doi.org/10.56238/sevened2025.036-145